Some aspects of the compatibility of mineral mining technologies (Rudarsko-geološko-naftni zbornik, 2018)
Sometimes in mining it is necessary to combine different extracting technologies within one enterprise.  So, in the paper the analysis of scientific and technical mining operations with combined technologies is carried out, the search for structure and their operation in the mining enterprise is performed. The processes and technological parameters of mineral extraction by two fundamentally different technologies are investigated in detail. Because of the introduction of additional technologies, it is possible to involve sub-standard reserves in the production process, an algorithm for determining the technological parameters is developed. This algorithm consists of criteria that make it possible to find compatibility of the work of one or more development technologies while maintaining an effective level of extraction. To do this, all processes at the enterprise are grouped: by degree of exploration, feasibility and economic efficiency. For each of them, certain coefficients were determined on the example of the operation of two specific combined technologies: the extraction of uranium ores and coal. For each group of criteria, certain coefficients are identified that allow assessing the feasibility of applying technology in their area. Their product is a general coefficient of compatibility, which shows the feasibility of introducing additional technology at the enterprise with the feasibility study. It defines the amount of funds invested in the development of an enterprise to achieve efficient mineral extraction with combined technologies within one enterprise. This point can be used to predict the grade variability of stockpiles from the origin source and the methodology allows characterizing the iron grades within stockpiles without any extra sampling.